A hotspot of Toxoplasma gondii Africa 1 lineage in Benin: How new genotypes from West Africa contribute to understand the parasite genetic diversity worldwide - (:unkn) unknown (My University, 2021)
Through international trades, Europe, Africa and South America share a long history of exchanges, potentially of pathogens. We used the worldwide parasite Toxoplasma gondii to test the hypothesis of a historical influence on pathogen genetic diversity in Benin, a West African country with a longstanding sea trade history. In Africa, T . gondii spatial structure is still non-uniformly studied and very few articles have reported strain genetic diversity in fauna and clinical forms of human toxoplasmosis so far, even in African diaspora. Sera from 758 domestic animals (mainly poultry) in two coastal areas (Cotonou and Ouidah) and two inland areas (Parakou and Natitingou) were tested for T . gondii antibodies using a Modified Agglutination Test (MAT). The hearts and brains of 69 seropositive animals were collected for parasite isolation in a mouse bioassay. Forty-five strains were obtained and 39 genotypes could be described via 15-microsatellite genotyping, with a predominance of the autochthonous African lineage Africa 1 (36/39). The remaining genotypes were Africa 4 variant TUB2 (1/39) and two identical isolates (clone) of Type III (2/39). No difference in terms of genotype distribution between inland and coastal sampling sites was found. In particular, contrarily to what has been described in Senegal, no type II (mostly present in Europe) was isolated in poultry from coastal cities. This result seems to refute a possible role of European maritime trade in Benin despite it was one of the most important hubs during the slave trade period. However, the presence of the Africa 1 genotype in Brazil, predominant in Benin, and genetic analyses suggest that the triangular trade was a route for the intercontinental dissemination of genetic strains from Africa to South America. This supports the possibility of contamination in humans and animals with potentially imported virulent strains.Author summary: The parasite Toxoplasma gondii is a worldwide-distributed pa
Keywords: African Research